Transcriptomics characteristics and differentiation of subcutaneous adipose tissue among Huainan pigs and its hybrid genetic populations - Yan, Taotao; Jia, Mingyang; Li, Jiaxi; Lan, Xianyong; Yuan, Liwei; Xing, Baosong; Pan, Chuanying; Lu, Qingxia; Wang, Jing (Frontiers in Veterinary Science, 2025)
IntroductionThe Huainan pig (HN) is known for its impressive litter size and exquisite meat quality. However, it also exhibits certain drawbacks such as excessive fat deposition, a relatively low percentage of lean meat percentage, and a slower growth rate. Crossbreeding with lean-type breeds, such as Large White, Landrace, and Berkshire can enhance offspring traits, and increase genetic diversity.MethodsIn this study we employed RNA-seq technology to identify differentially expressed genes (DEGs) in subcutaneous adipose tissue (SAT) samples from HN pigs and their crosses with multiple breeds (with three replicates per group).ResultsIn the SAT of Huainan × Berkshire pigs (BH), Huainan × Yorkshire pigs (YH), and Huainan × Landrace pigs (LH), numerous key functional genes were identified, including LIPG, PLIN2, CPT1A, KLF9, CCND1, LDLR, ACSL1, ACLY and ANGPTL4. Functional enrichment analysis revealed that DEGs were primarily involved in several key pathways in BH, including the peroxisome proliferator-activated receptor (PPAR) signaling, metabolic pathways, arachidonic acid metabolism, and arginine/proline metabolism. Similarly, in LH, DEGs were associated with PPAR, cyclic adenosine monophosphate (cAMP) signaling, mitogen-activated protein kinase (MAPK), and the arginine/proline pathway. In contrast, the main pathways in YH were slightly different, including MAPK, fatty acid elongation, arginine/proline metabolism, and glycine/serine/threonine metabolism. Compared to HN, the differential genes in BH, LH, and YH showed a reduced fat deposition. However, in comparison, LH has a stronger subcutaneous fat deposition ability. Notably, LH exhibited a stronger tendency for subcutaneous fat deposition than the other two groups, while YH had the lowest fat deposition capacity.ConclusionIn conclusion, these findings offer valuable insights and provide a foundation for future research on the molecular mechanisms underlying fat deposition in pigs.